2018
DOI: 10.37358/rc.18.10.6608
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Type Fatty Acid-Binding Protein (H-FABP) in Patients with Type 2 Diabetes Beneficiaries of Rehabilitation Program Post Coronary Artery Bypass Grafting

Abstract: Heart-type fatty acid-binding protein (H-FABP) is a non-invasive bio-marker, with high sensitivity and specificity, being capable to point out the myocardial injury and to predict major adverse cardiovascular events (MACE). Cardiac rehabilitation program, through a complex and sustained post-interventional management plays an important role in reducing the plasma levels of H-FABP. In the study, which included 120 post-coronary artery bypass (CABG) patients, we analyzed the link between low levels of general po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Table (4) showed that concerning P wave duration, there was no statistical difference between both groups (p = 0.131) where P wave duration in POAF was 113.98 ± 14.36 ms compared to 112.76 ± 13.62 ms in -ve POAF group. As regards p wave dispersion, there was no statistical difference between both groups (p = 0.213) where P wave dispersion in POAF was 63.6 ± 15.23 ms compared to 61.51 ± 12.66 ms in -ve POAF group.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Table (4) showed that concerning P wave duration, there was no statistical difference between both groups (p = 0.131) where P wave duration in POAF was 113.98 ± 14.36 ms compared to 112.76 ± 13.62 ms in -ve POAF group. As regards p wave dispersion, there was no statistical difference between both groups (p = 0.213) where P wave dispersion in POAF was 63.6 ± 15.23 ms compared to 61.51 ± 12.66 ms in -ve POAF group.…”
Section: Resultsmentioning
confidence: 89%
“…After mitral valve surgery (MVS), the probability of POAF was greater than after coronary artery bypass grafting (CABG) or surgery. Clearly, postoperative POAF should be avoided and managed (4) . In order to identify high-risk patients before surgery and provide them with appropriate preventive regimens, several approaches have been evaluated for calculating the risk of developing POAF (5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation